25(Oh)D levels and skinfolds thickness in athletes - Ksiazek, A.; Zagrodna, A.; Pietras, J. (Human Movement, 2015)
Purpose. The aim of our study was to assess the relationship between 25(OH)D levels and skinfold thickness in Poland`s premier league (Ekstraklasa) football players. Methods. We enrolled 43 Poland`s premier league football players. The mean age was 22.7 ± 5.3 years. Serum levels of 25(OH)D were measured by electrochemiluminescence (ECLIA) using the Elecsys system (Roche, Switzerland). Skinfold measurements were taken with a Harpenden-type skinfold calliper body fat tester, characterised by a constant pressure of 10 g/mm2. Results. Our study showed decreased serum 25(OH)D levels in 74.4% of the professional football players. We did show a statistically significant negative correlation between the 25(OH)D levels and the biceps skinfold thickness (r = -0.33), iliac crest skinfold thickness (r = -0.43), the sum of all the studied parameters (r = -0.5) and percentage of body fat (r = -0.49). Conclusions. Our results suggest that athletes with higher content of the adipose tissue may be at a higher risk of vitamin D deficiency, and that 25(OH)D levels need to be monitored in professional athletes, particularly during the winter season.